Draft Eighth Five Year Plan 1990-95 Volume-I Government of Karnataka - Planning Commission (Planning Commission, 1990)
Karnataka is a middle order State in the country accounting for about 6.3 per cent of geographical area and 5.4 per cent of population (1981) of the country. The State is endowed with rich natural resources. But the State had started with a weak economic base at the time of Reorganisation (1956).
Government of Karnataka